2014
DOI: 10.1186/1758-5996-6-55
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of epicardial adipose tissue in patients with type 2 diabetes mellitus

Abstract: BackgroundEpicardial adipose tissue (EAT), visceral fat depot of the heart, was found to be associated with coronary artery disease in cardiac and non-cardiac patients. Platelet-to-lymphocyte ratio (PLR) and neutrophil-to-lymphocyte ratio (NLR) were introduced as potential markers to determine inflammation in various disorders. Recently, atherogenic index of plasma (AIP) was found to be closely associated with atherosclerosis in general population. Waist circumference is commonly used to assess the risk factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 50 publications
(53 reference statements)
2
31
0
4
Order By: Relevance
“…A further 196 studies lacked sufficient data, 5 were studies of animals, and 1 was excluded because it was not published in English. Therefore, our final analysis included 13 studies (1102 patients with DM and 813 healthy control subjects) that measured EFT in a DM group and a control group [20,21,[27][28][29][30][31][32][33][34][35][36][37] (Fig. 1).…”
Section: Description Of the Studiesmentioning
confidence: 99%
“…A further 196 studies lacked sufficient data, 5 were studies of animals, and 1 was excluded because it was not published in English. Therefore, our final analysis included 13 studies (1102 patients with DM and 813 healthy control subjects) that measured EFT in a DM group and a control group [20,21,[27][28][29][30][31][32][33][34][35][36][37] (Fig. 1).…”
Section: Description Of the Studiesmentioning
confidence: 99%
“…Kardiyovasküler hastalıklarda da prognostik öneme sahip olduğu gösterilmiştir (7,8) . Yapılan çalışmalarda TLO'nun CHA2DS2- VASc skorunun komponentleri olan diabetes mellitus, hipertansiyon ve koroner arter hastalığının varlığı ile artış gösterdiği saptanmıştır (7,12,39) . Türkiye'den Uçar ve arkadaşları yaptıkları çalışmada koroner arter hastalığı yaygınlığı ile TLO arasında ciddi bir ilişki olduğu saptanmıştır (40) .…”
Section: Discussionunclassified
“…There are studies aiming to determine the relationship between inflammatory markers and EFT. Akbas reported that NLR and PLR were correlated with EFT but only the waist circumference was independently associated with EFT in diabetic patients 22 . In our study, there was no difference between the groups in terms of the PLR, but there was a positive correlation between EFT and PLR in diabetic patients.…”
Section: Table 2 the Correlation Between Epicardial Fat Thickness Anmentioning
confidence: 99%